Anticataract activity of ethanolic extract from Hippobroma longiflora (L.) G.Don leaves: Ex vivo investigation - Eva Imelda; Khairan Khairan; Rodiah R. Lubis; Pati Kemala; Utari Zulfiani; Suci Rahayu; Ghazi M. Idroes; Sarra M. Adev; Nur B. Maulydia; Rinaldi Idroes (GarVal Editorial Ltda., 2023)
Context: In Aceh, Hippobroma longiflora, known as kitolodby the locals, is believed to possess medicinal benefits such as anticataract. Aims: To investigate the anticataract activity of ethanolic extract from H. longiflora leaves ex vivo. Methods: The dried fine powder of H. longiflora was macerated using ethanol at room temperature, and the concentrated extract was prepared in concentrations ranging from 100 to 300 μg/mL. The cataract model was established by using goat lens induced with H2O2 and later exposed to the extract for treatment. Anti-cataract activity was assessed by observing the change in lens opacity. Further, malondialdehyde levels and activities of endogenous antioxidants (superoxide dismutase, glutathione peroxidase, and catalase). Results: The apparent cataract opacity reduced after the exposure of the extract was observed macroscopically. The cataract eyes experienced a significant increase (p<0.05) in malondialdehyde level and a significant reduction (p<0.05) in the activities of superoxide dismutase, glutathione peroxidase, and catalase. The pathologic conditions could be reversed by introducing the extract with a concentration as low as 100 μg/mL (p<0.05). Conclusions: The ethanolic extract of H. longiflora leaf has a potential anticataract effect by ameliorating oxidative stress-related biocompounds.